AKTIVITAS ANTI RAYAP TANAH (Coptotermes curvignathus Holmgren) TIGA FRAKSI EKSTRAK KAYU PELANJAU (Pentaspadon Motleyi Hook.f) - Yusro, Fathul (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Aim of this research is to know activity of tree fractions (diethyl ether, ethyl acetate and residue) pelanjau wood extracts (Pentaspadon motleyi Hook.f) against Coptotermes curvignathus Holmgren. Method of the research was anti termites test with parameter termites mortality and samples weight lost. Research result show highest mortality from ethyl acetate, diethyl ether and residue fractions with 100% mortality in concentration â‰¥5%, â‰¥7,5% and 10%, respectively. Sample weight lost from ethyl acetate, diethyl ether and residue fractions was 9,91-3,89%; 34,37-13,50% and 35,25-18,21%, respectively. Keywords: Pelanjau wood (Pentaspadon motleyi Hook.f), tree fractions, termites, Coptotermes curvignathus Holmgren